Low-molecular-weight fucoidan enhances the proangiogenic phenotype of endothelial progenitor cells - Zemani, Faouzia; Benisvy, Danielle; Galy-Fauroux, Isabelle; Lokajczyk, Anna; Colliec-Jouault, Sylvia; Uzan, Georges; Fischer, Anne Marie; Boisson-Vidal, Catherine (Biochemical pharmacology, 2005)
Endothelial progenitor cell (EPC) transplantation is a potential means of inducing neovascularization in vivo. However, the number of circulating EPC is relatively small, it may thus be necessary to enhance their proangiogenic properties ex vivo prior to injection in vivo. Fucoidan has previously been shown to potentiate in vitro tube formation by mature endothelial cells in the presence of basic fibroblast growth factor (FGF-2). We therefore examined whether fucoidan, alone or combined with FGF-2, could increase EPC proangiogenic potency in vitro. EPC exposure to 10 μg/ml fucoidan induced a proangiogenic phenotype, including cell proliferation ( p < 0.01) and migration ( p < 0.01); moreover, differentiation into vascular cords occurred in the presence of FGF-2 ( p < 0.01). This latter effect correlated with upregulation of the cell-surface #α6 integrin subunit of the laminin receptor ( p < 0.05). Compared to untreated HUVEC, untreated EPC #α6 expression and adhesion to laminin were enhanced two-fold. Fucoidan treatment further enhanced HUVEC but not EPC adhesion to laminin. These results show that fucoidan enhances the proangiogenic properties of EPC and suggest that ex vivo fucoidan preconditioning of EPC might lead to increased neovascularization when injected into ischemic tissues.